Pengaruh Experiential Learning Terhadap Motivasi Siswa Pada Pembelajaran Geografi Di Kelas XI SMAN 1 Tigo Nagari - Amelia, Atisa; Ratna Wilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the experiential learning model on the motivation and learning outcomes of geography student of class XI of SMAN 1 Tigo Nagari. This study uses a quantitative method with a quasi-experimental approach, the sample was selected through a purposive sampling technique consistingof an experimental class (XI FASE F4) and a control class (XI FASE F6). Data were collected through observations, questionnaires, and pretest and postest. Data were then analyzed using t-tests and N-Gain tests. The results showed that the implementation of the experiential learning model performed very well, with an observation score of 88,7%. Based on the hypothesis test, a significant effect was found on student motivation and learning outcomes with a significance value of 0,000 < 0,05. The effectiveness of the model was confirmed by the results of the N-Gain test, where the experimental class achieved a score of 66,15% (effective category), while the control class only achieved 21,41% (ineffective category). This concludes that the experiential learning model is more effective in improving student motivation and learning outcomes than conventional methods.